Incidence of gallium-67 citrate uptake in brown adipose tissue in neonates. (December 2013) - Rakheja, Rajan; Makis, William; Lambert, Raymond; Turpin, Sophie
Aims: Increased 18 F-fluorodeoxyglucose uptake within active brown adipose tissue (BAT) on an 18 F-fluorodeoxyglucose PET/CT study is a known pitfall that has been well described in the literature. We have noted a similar phenomenon occurring in gallium-67 studies performed on neonates, which introduces an undesirable element of complexity when evaluating for the presence of infection or malignancy. Since the incidence of gallium-67 uptake in BAT in neonates has not been previously described in the literature, the goal of this study was to evaluate the pattern of uptake and its incidence in our neonatal patient population.Materials & methods: A complete review was performed of the Hospital Ste-Justine's (QC, Canada) database of nuclear medicine studies carried out from June 2001 to May 2011, revealing 64 total body gallium-67 scans of neonates (carried out within the first 28 days after birth). These studies were reviewed for BAT gallium-67 uptake.Results: Ten of out 64 patients had gallium-67 uptake in a pattern typical for BAT distribution (incidence of 16%).Conclusion: We observed a significant percentage of neonates that demonstrated gallium-67 uptake in BAT. As total body gallium scans are not routinely performed in the neonatal age group at most institutions, we feel that nuclear medicine specialists should be aware of gallium-67 uptake in BAT tissue, as a potential pitfall that may be confused with pathologic uptake.